Pengaruh mekanisme Corporate Governance, Profitability, dan Firm Size terhadap pengungkapan Corporate Social Responsibility - Shelby Edinov; Rida Rahim; Masyhuri Hamidi (Politeknik Ganesha Medan, 2022)
In this study was conducted to determine the effect of corporate governance mechanisms, profitability and firm size on the disclosure of corporate social responsibility (CSR) of Indonesian Stock Exchange companies for the 2018-2020 period. The independent variables in this study include the audit committee, independent board of commissioners, foreign ownership, public ownership, ROA, ROE and firm size as well as growth control variables, debt equity ratio and current assets. Meanwhile, the disclosure of CSR is used as the dependent variable. The sampling technique was carried out by purposive sampling so that 36 companies were used as research samples. The data analysis technique used in this study is panel data regression analysis, where the results obtained by each variable on CSR disclosure are as follows; the audit committee has a positive and insignificant effect, the independent board of commissioners has a positive and insignificant effect, foreign ownership has a negative and insignificant effect, public ownership has a positive and insignificant effect, ROA has a negative and insignificant effect, ROE has a positive and insignificant effect, and firm size positive and significant effect. The results of the simultaneous test conducted show that the audit committee, independent board of commissioners, foreign ownership, public ownership, ROA, ROE and firm size have no effect on CSR disclosure.CSR disclosure